BiVO4 Photoanode with Exposed (040) Facets for Enhanced Photoelectrochemical Performance - Ligang Xia; Jinhua Li; Jing Bai; Linsen Li; Shuai Chen; Baoxue Zhou (Nano-Micro Letters, 2017)
Abstract A BiVO4 photoanode with exposed (040) facets was prepared to enhance its photoelectrochemical performance. The exposure of the (040) crystal planes of the BiVO4 film was induced by adding NaCl to the precursor solution. The as-prepared BiVO4 photoanode exhibits higher solar-light absorption and charge-separation efficiency compared to those of an anode prepared without adding NaCl. To our knowledge, the photocurrent density (1.26 mA cm−2 at 1.23 V vs. RHE) of as-prepared BiVO4 photoanode is the highest according to the reports for bare BiVO4 films under simulated AM1.5G solar light, and the incident photon-to-current conversion efficiency is above 35% at 400 nm. The photoelectrochemical (PEC) water-splitting performance was also dramatically improved with a hydrogen evolution rate of 9.11 μmol cm−2 h−1, which is five times compared with the BiVO4 photoanode prepared without NaCl (1.82 μmol cm−2 h−1). Intensity-modulated photocurrent spectroscopy and transient photocurrent measurements show a higher charge-carrier-transfer rate for this photoanode. These results demonstrate a promising approach for the development of high-performance BiVO4 photoanodes which can be used for efficient PEC water splitting and degradation of organic pollutants.